Verbalization of Lexical and Phraseological Means in the Category of Language Consciousness - Mardiyev T. K. (International Journal on Integrated Education, 2022)
In the category of linguistic consciousness, in the verbalized system of lexical and phraseological means, the whole life of a person, perceived in the categories of social consciousness, is fixed, interpreted and generalized. In the linguistic consciousness, which is formed in the content of the words of a particular language, the national-subjective image of the world finds its expression, and the universal stereotypes inherent in it are also reflected. Language consciousness is often equated with a set of ideas, guidelines and stereotypes based on direct everyday experience and features that dominate people's social life.